The Thought of Emmanuel Levinas and its Relevance to The- ology - Correa, Oscar A. (Teología, 2019)
E. Levinas proposes a way of understanding the subjectivity that differs from the transcendental and constituent conscience of the modern Philosophy. It is not the Being, not even the knowledge, what determines the subjectivity but the Good that precedes the being and calls to the responsibility for the other one with a Saying pre- vious to the linguistic discourse. The trace of that call in the face of the other one refers to an Infinite that demands from the alterity. God does not come through the unveiled being but from the absolute difference between the Same and the Other one, where that one is alloted to this one in the way one-for-the-other one. The sugges- tions of this thinker question indirectly the theological work that is built over the being and it only gives place to a way of thematic knowledge.